Colossoma macropomum females can reproduce more than once in the same reproductive period - Pires, Luana Barbosa; Corrêa Filho, Ruy Alberto Caetano; Sanches, Eduardo Antonio [UNESP]; Romagosa, Elizabeth; Silva, Thiago Gonsalo da; Rech, Silvia; Streit, Danilo Pedro; Povh, Jayme Aparecido (Elsevier, 2018)
The aim of the present study was to evaluate induced reproduction in Colossoma macropomum females at the beginning of the reproductive period and 75 days after the first spawning in which reproduction was induced. The experiment was conducted in Nova Mutum, MT, Brazil. Eight 4-year-old C. macropomum females with an average body weight of 6.7 ± 2.4 kg were used. Hormonal induction was performed at the beginning of the reproductive period and repeated 75 days after the first spawning. The following variables were then evaluated: weight of released oocytes, production index, absolute fecundity, oocyte diameter, fertilization rate, and hatching rate. Of the eight females that spawned during the first hormonal induction, three (37.5%) spawned again 75 days after the first spawning. Two females died after the first induced spawning. None of the means of the evaluated variables differed between the two induced spawnings, except for fertilization rate, which was greater (P < 0.05) with the first spawning (88.8 ± 6.1%) than in the second (74.1 ± 10.4%). The results of the present study indicate that C. macropomum females can reproduce again 75 days after a first induced spawning.
Keywords: Hormonal induction; Rheophilic